Leccinum vulpinum Watling induces DNA damage, decreases cell proliferation and induces apoptosis on the human MCF-7 breast cancer cell line - Reis, Filipa S. (2016)
The current work aimed to study the antitumour activity of a phenolic extract of the edible mushroom Leccinum vulpinum Watling, rich essentially in hydroxybenzoic acids. In a first approach, the mushroom extract was tested against cancer cell growth by using four human tumour cell lines. Given the positive results obtained in these initial screening experiments and the evidence of some studies for an inverse relationship between mushroom consumption and breast cancer risk, a detailed study of the bioactivity of the extract was carried out on MCF-7 cells. Once the selected cell line to precede the work was the breast adenocarcinoma cell line, the human breast non-malignant cell line MCF-10A was used as control. Overall, the extract decreased cellular proliferation and induced apoptosis. Furthermore, the results also suggest that the extract causes cellular DNA damage. Data obtained highlight the potential of mushrooms as a source of biologically active compounds, particularly with antitumour activity.